Pelatihan Sekolah Desain Dan Implementasi Di Berbagai Aspek Kehidupan Sebagai Upaya Perkembangan Teknologi Di Desa Sadar Jaya - Seno Andri; Fadhur Rahman Halim; Pergo Pergo; Eka Winarti; Ayesa Anastasia Agusman; Dita Amanda; Melisa Samosir; Prima Ronaldo Siagian; Novelia Rahmi; Nabilah Putri Awaliah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
The rapidly increasing progress of the times requires us to be able to keep up with the developments of the times. One thing that continues to improve rapidly as time goes by is digital technology. Digital technology is currently very necessary for every aspect of life in the fields of education, government, health and other aspects. One of the current focuses is graphic design, where graphic design is very necessary to support aspects of human life. To equip the younger generation with the basics of graphic design to make it easier to participate in current developments, design schools are carried out. This design school is focused on training in using the Canva application. Graphic design is a form of communication through visualization so it can be a very effective form of communication media. This design school training is aimed at training every element of society to be able to grow and develop their soft skills so that they are able to participate and compete in this era to become someone who is successful and successful in developing creativity and quality of work.